Dapagliflozin decreases atherosclerotic plaque instability via regulating macrophage pyroptosis. (14th October 2021) - Xu, L; Dai, Y; Yao, K; Yang, H; Sun, A; Qian, J; Ge, J
Abstract: Background: Vulnerable plaques are characterized by infiltration of inflammatory cells, playing a key role in the progression of acute coronary events. It's important to clarify the inflammatory mechanism of unstable plaque formation. Several clinical trials have demonstrated that dapagliflozin could reduce major adverse cardiac events in whether diabetic or non-diabetic patients. However, the underlying cardioprotective mechanism of dapagliflozin remains unclear. This study was aimed to investigate the role of dapagliflozin in regulating macrophage pyroptosis and vulnerable plaque formation. Methods: 20 ApoE−/− mice (control) were fed with high fat diet while another 20 ApoE−/− mice were challenged with high fat diet plus dapagliflozin for 12 weeks. The extent and instability of atherosclerotic plaque was determined by oil-red staining, HE staining, immunofluorescence staining and electron microscopy. Changes in subsets of immune cells were evaluated by flow cytometry. Plasma cytokines were assessed by ELISA. Microarray analysis was applied to detect gene expressions while Western blot and real-time PCR was used to assess gene expression levels. Results: Morphology studies revealed that dapagliflozin could inhibit plaque formation and reduce instability in ApoE−/− mice. FACS data showed that dapagliflozin could decrease CD11b+Ly6Chigh M1 macrophages differentiation and inhibit foam cells formation in ApoE−/− mice. Microarray analysis and in vitro studies exhibited that dapagliflozin could induce the down regulation of NLRP3, caspase-1, IL-1β, IL-18 and MMP-7/10/12/14 to retard macrophage pyroptosis and foam cell formation. Conclusions: We have characterized a novel role for dapagliflozin in modulating atherosclerotic lesion development and progression. We envision that this study may provide several potential therapeutic targets for treatment of acute coronary syndromes. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Shanghai Sailing Program